LEARNING VOCABULARY WITH THE CLASSROOM LANGUAGE - N. A. Shamsutdinova,; Alaydinova Maharramxon, (Ustozlar uchun, 2025)
This article explores the selection and strategic use of vocabulary within the classroom setting, focusing on how specific word choices can effectively engage students and facilitate vocabulary acquisition through classroom language.